Defining breeding goals and breeding strategies for improving the productivity of cattle breeds and buffaloes in African production systems - Mrode, Raphael A.; Mbah, D.A.; Tawah, C.L.; Ojango, Julie M.K.; Peters, S.O.; Ibeagha-Awemu, E.M.; Opoola, O.; Houaga, I.; Osei-Amponsah, R.; Okpeku, M.; Rege, J.E.O. (Springer, 2025)
The previous chapter discussed the fundamental concepts and principles that underpin the definition of breeding goals and strategies. In this chapter, some of the peculiar aspects of breeding goals and strategies for the improvement of cattle and buffaloes in Africa, in addition to lessons drawn from past cattle improvement projects, are examined. The chapter is broadly presented in four sections. Section 16.1 deals with the concept of breeding goals in the context of the most dominant production system in Africa and examines evolving trends in breeding goals that incorporate health and welfare considerations. This is followed by Sect. 16.2 which presents the fundamental role of market situations in the design of breeding goals and the influence of some regional institutions and policies on breeding programmes. Breeding goals for beef and dairy cattle production and some lessons from the design of breeding goals from previous breeding programmes were then outlined. Section 16.3 considers breeding strategies aimed at promoting sustainable animal production systems in African diverse environments. It then delves into the different breeding strategies including breed substitution and cross-breeding, selection approaches for cattle improvement, nucleus or group breeding schemes, community-based livestock breeding schemes and unplanned selection programmes. Section 16.3.2 is focused on emerging molecular and reproductive technologies in breeding strategies relevant to genetic improvement in various cattle and buffalo production systems in Africa. It deep dived into the different technologies as follows: molecular and genomic technologies for breeding strategies, reproductive technologies for African cattle and buffalo breeding strategies, nucleus breeding schemes for assisted reproduction in cattle and buffaloes, in vitro fertilization, somatic cell nuclear transfer and multiple ovulation and embryo transfer. The chapter concludes with some final remarks and future perspectives.